Inhibition of PTEN promotes osteointegration of titanium implants in type 2 diabetes by enhancing anti-inflammation and osteogenic capacity of adipose-derived stem cells - Zhang, Guanhua; Song, Shuang; Chen, Zijun; Liu, Xiangdong; Zheng, Jian; Wang, Yuxi; Chen, Xutao; Song, Yingliang (Frontiers in Bioengineering and Biotechnology, 2024)
The low osteogenic differentiation potential and attenuated antiinflammatory effect of adipose-derived stem cells (ADSCs) from animals with type 2 diabetes mellitus (T2DM) limits osseointegration of the implant. However, the underlying mechanisms are not fully understood.Methods: Western blotting and qRT-PCR analyses were performed to investigate the effects of PTEN on the osteogenic capacity of ADSCs of T2DM rats (TADSCs). We conducted animal experiments in T2DM-Sprague Dawley (SD) rats to evaluate the osteogenic capacity of modified TADSC sheets in vivo. New bone formation was assessed by micro-CT and histological analyses.In this study, adipose-derived stem cells of T2DM rats exhibited an impaired osteogenic capacity. RNA-seq analysis showed that PTEN mRNA expression was upregulated in TADSCs, which attenuated the osteogenic capacity of TADSCs by inhibiting the AKT/mTOR/HIF-1α signaling pathway. miR-140-3p, which inhibits PTEN, was suppressed in TADSCs. Overexpression or inhibition of PTEN could correspondingly reduce or enhance the osteogenic ability of TADSCs by regulating the AKT/mTOR/HIF-1α signaling pathway. TADSCs transfected with PTEN siRNA resulted in higher and lower expressions of genes encoded in M2 macrophages (Arg1) and M1 macrophages (iNOS), respectively. In the T2DM rat model, PTEN inhibition in TADSC sheets promoted macrophage polarization toward the M2 phenotype, attenuated inflammation, and enhanced osseointegration around implants.Conclusions: Upregulation of PTEN, which was partially due to the inhibition of miR-140-3p, is important for the attenuated osteogenesis by TADSCs owing to the inhibition of the AKT/mTOR/HIF-1α signaling pathway. Inhibition of PTEN significantly improves the anti-inflammatory effect and osteogenic capacity of TADSCs, thus promoting peri-implant bone formation in T2DM rats. Our findings offer a potential therapeutic approach for modifying stem cells derived from patients with T2DM to enhance osseointegration.